The Issues of Expert Opinion Evaluation on Forensic Transport Examinations - N. N. Il’in (Теория и практика судебной экспертизы)
One of the factors adversely affecting the quality of crime investigations is the misuse and misapprehension of forensic evidence in proving. An essential part of solving this problem is a more effective use by investigative bodies of specialized knowledge in the form of forensic examinations. In particular, when investigating crimes concerning the violation of traffic rules and transport operation, an investigator should thoroughly evaluate an expert’s opinion in the field of transport and technical forensic examinations. The author studied the expert practice on these forensic examinations, indicating the existing significant number of expert opinions in the “probable” form. In the author’s opinion, the main reasons for such opinions are the presence of probable conclusions about the causes of the traffic accident in the materials of the internal investigation submitted for examination and the insufficient information content of the initial data. The analysis of the errors made by experts on forensic transport examinations indicates the need to study the received conclusions thoroughly, look closely not only into the conclusions themselves but also into the content of the research part, which will allow to timely recognize the incompetence of the study, detect technical errors, as well as the inconsistency with the conclusions on other circumstances established in a criminal case.